Perancangan E-Catalog sebagai Media Promosi Produk Wisata Bahari PT Tripgo Wisata Internasional - Femmylia Dwi Putri; Nurhayati, Atikah; Gumilar, Iwang; Dhahiyat, Ahmad Prawira; Kristiadhi, Fanny (Business Preneur: Jurnal Ilmu Administrasi Bisnis, 2026)
This study aims to design an interactive e-catalog as a digital promotional medium for marine tourism products of PT Tripgo Wisata Internasional using a mixed methods approach within the Design Thinking framework (empathize, define, ideate, prototype, and test). Data were collected through interviews, observations, and questionnaires administered to the company’s internal team and prospective tourists. The results show that the e-catalog developed with Canva Pro was rated “Excellent” in terms of visual design, content, navigation, and functionality, while also increasing tourists’ interest, willingness to recommend, and confidence in choosing Tripgo’s tourism products. Therefore, the e-catalog has the potential to serve as an effective, user-oriented digital promotional tool that strengthens Tripgo’scompetitiveness in the marine tourism industry. Keywords: e-catalog, marine tourism, design thinking